Lance lacewings of the world (Neuroptera: Archeosmylidae, Osmylidae, Saucrosmylidae): review of living and fossil genera - Winterton, Shaun L.; Martins, Caleb Califre; Makarkin, Vladimir; Ardila-Camacho, Adrian; Wang, Yongjie (Zootaxa, 2019)
The genera of the lance lacewing family Osmylidae (Neuroptera) and extinct allied families (Archeosmylidae, Saucrosmylidae) are reviewed. A key to living Osmylidae genera of the world is presented. Each genus is diagnosed and figured with a checklist of species included for each. New, revised or support for previous taxonomic changes include the following: Nuddsia Menon & Makarkin, 2008 (= Burmaleon Myskowiak et al., 2016 syn. nov.); Kempynus Navás, 1912 (= Clydosmylus New 1983a syn. nov.); Osmylus Latreille, 1802 (= Hyposmylus McLachlan; Dictyosmylus Navás, 1910; Plesiosmylus, Makarkin, 1985; Plethosmylus Krüger, 1913a); Parosmylus Needham, 1909 (= Mesosmylus Krüger, 1913c; Phlebosmylus Navás, 1928 syn. nov.); Thaumatosmylus Krüger, 1913a (= Glenosmylus Krüger, 1913a syn. nov.). New classification changes include: Mesomylidus Jepson, 2012 and Petrushevkia Martynova, 1958 are transferred to Protosmylinae; Lahulus Navás, 1930 is placed in Osmylinae; Stenosmylina Jepson et al., 2009 is transferred to Eidoporisminae. Cratovoluptia Martins-Neto & Rodrigues, 2009 is removed from Osmylidae and transferred to Ithonidae, while Cratosmylus Myskowiak et al., 2015 is transferred to Nymphidae. Idiastogyia Lin, 1986 and Yanosmylus Ren in Ren et al., 1995 are excluded from Osmylidae and placed as incertae sedis in Neuroptera.